Systematic design of high-performance CO gas sensor based on QCM and the impact of environmental humidity - Luyu Wang; Chenghai Ruan; Chunyang Yu; Jia Song (Química Nova)
The quartz crystal microbalance (QCM) sensing platform detects a wide variety of gases, yet lacks a system designed specifically for carbon monoxide (CO) gas. Here, we utilized ceric dioxide (CeO2) nanorods as the sensing material and coated them onto the QCM surface to construct a novel QCM sensor. This sensor is capable of detecting CO concentrations as low as 500 ppb and exhibits satisfactory sensitivity, response speed, selectivity, repeatability, and long-term stability. The sensing mechanism and the influence of environmental humidity on this sensor were also explored. This work broadens the application scope of QCM sensing platform and provides an additional solution for detecting CO at room temperature.